ANALISIS FIRM SIZE, GROWTH OPPORTUNITY DAN TOTAL ASSET TURN OVER TERHADAP RETURN ON ASSET KASUS PADA PERUSAHAAN FOOD BEVERAGES - Nailal Husna (Jurnal Apresiasi Ekonomi, 2016)
The object of this study is the Food Beverages company whose shares are listed on the Indonesia Stock Exchange 2009 until 2013 period, and the sample is a company that is always consistent issued financial statements in the period of observation. The purpose of this study analyzed the factors that caused the decline or fluctuations in the value of its profitability. And the research variables are Return On Asset (Y), Firm Size (X1), Growth Opportunity (X2), Total Asser Turn Over (X3). Based on the analysis and discussion of the results of hypothesis testing then the conclusion is the Firm Size significantly influence the Return On Asset, Growth Opportunity whereas no significant effect on Return On Assets, And On variable Total Asset Turn Over significantly influence the Return On Asset. Keywords : Firm Size, Growth Opportunity, Total Asser Turn Over, Return On Asset, Food Beverage.